THE THEORETICAL FOUNDATIONS OF PREPARING FUTURE TEACHERS FOR COLLABORATIVE PROFESSIONAL ACTIVITY - Taylakova Gulnoz Mamatkarimovna (American Journals, 2025)
This scientific article provides a comprehensive theoretical and methodological analysis of the preparation of future teachers for collaborative professional activity within the framework of educational technologies and innovative pedagogy. Special attention is given to global transformations in education, digitalization processes, models of collaborative learning, mechanisms for developing collaborative competencies in higher education, and the role of interaction and communication culture in teacher preparation. The study elaborates on constructivist, cooperative, collaborative, communicative, and sociocultural paradigms of collaborative learning, as well as the principles of integrating modern pedagogical technologies (blended learning, project-based learning, team-based learning, digital collaboration tools) into the professional training of future teachers. The structural composition of collaborative competence, its theoretical interpretations, innovative mechanisms for its development during practicum, and its interrelation with the professional maturity of the teacher are systematically explored. The research findings form a scientific and practical basis for modernizing teacher education, improving methodological systems aimed at collaboration, and enhancing the professional competitiveness of future teachers.
Keywords: Collaborative learning, collaborative competence, innovative pedagogy, educational technologies, future teachers, cooperative learning, digital collaboration, professional training.